2022
DOI: 10.1088/1367-2630/ac6cfd
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic dynamics of Bose–Einstein condensate induced by density-dependent gauge field

Abstract: In this work we study the effect of density-dependent gauge field on the collective dynamics of a harmonically trapped Bose-Einstein condensate, beyond the linear response regime. The density dependent gauge field, as a backaction of the condensate, can in turn affect the condensate dynamics, resulting in highly nonlinear equations of motion. The dipole and breathing oscillations of the condensate along the direction of gauge field are coupled by this field. We find that, in the presence of this coupling, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…In a harmonic trap, it has been shown that the current density term of Eq. 4.26 results in coupling between the monopole and dipole collective modes leading to chaotic dynamics for large amplitude oscillations [277][278][279]. SIMULATION (a) (b) From the gauge theory perspective, it can be seen that the monopole mode corresponds to periodic compressions and expansions of the gas meaning periodic changes in density and a periodic electric driving force which couples to the centre of mass motion and excites the dipole mode.…”
Section: 2(a)mentioning
confidence: 99%
“…In a harmonic trap, it has been shown that the current density term of Eq. 4.26 results in coupling between the monopole and dipole collective modes leading to chaotic dynamics for large amplitude oscillations [277][278][279]. SIMULATION (a) (b) From the gauge theory perspective, it can be seen that the monopole mode corresponds to periodic compressions and expansions of the gas meaning periodic changes in density and a periodic electric driving force which couples to the centre of mass motion and excites the dipole mode.…”
Section: 2(a)mentioning
confidence: 99%
“…Chiral BECs have been predicted to display a number of unconventional properties, including the existence of chiral solitons 52,[68][69][70] , density-dependent persistent currents and anomalous expansion dynamics 52 , unconventional collective modes [71][72][73] , and peculiar vortex patterns 74,75 . Previous works from the group of Prof. Öhberg group viewed these properties as a result of the current-density interaction term of eq.…”
Section: Properties Of a Chiral Bec From A Gauge Theory Perspectivementioning
confidence: 99%
“…For instance, Refs. [71][72][73] showed that the current-density term of the eGPE eq. (2.32) leads to a coupling of the monopole and dipole collective modes of the system, eventually leading to chaotic dynamics.…”
Section: Electric Fieldmentioning
confidence: 99%